-16+x-1=13-16+8

Simple and best practice solution for -16+x-1=13-16+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -16+x-1=13-16+8 equation:


Simplifying
-16 + x + -1 = 13 + -16 + 8

Reorder the terms:
-16 + -1 + x = 13 + -16 + 8

Combine like terms: -16 + -1 = -17
-17 + x = 13 + -16 + 8

Combine like terms: 13 + -16 = -3
-17 + x = -3 + 8

Combine like terms: -3 + 8 = 5
-17 + x = 5

Solving
-17 + x = 5

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '17' to each side of the equation.
-17 + 17 + x = 5 + 17

Combine like terms: -17 + 17 = 0
0 + x = 5 + 17
x = 5 + 17

Combine like terms: 5 + 17 = 22
x = 22

Simplifying
x = 22

See similar equations:

| -11=-x | | 1-8r=-(3r-1) | | z^2+(3+i)z+3i=0 | | lnx+ln(x+7)=0 | | -18-4x=-6x+14 | | -8(8+4x)=23-3x | | X+x+2=654 | | 5x-20=3x-60 | | 17(t-3)+4=7(3t+3)-12 | | X-6=4x+2 | | -7+n=-4-8(-6+2n) | | 0.01=x(1-x) | | x+(0.01x-1)=1 | | 2(x+7)=-36 | | 2xy=0.02 | | 3x-4y=-6 | | 25y^2+16=0 | | 6(x+1)+3(2-x)=2(2x-1)-(4-x) | | 3*0-4y=-6 | | p^2-50=0 | | 0.01=(1-x)x | | (5x-1)+(13-x)=24 | | x^2+5=9-6x+x^2 | | 4d^2+81=0 | | -3x=2y | | y-6=0.5x | | 0.18(12)+0.03x=0.09(24+x) | | 3(4x-3)-19=8x-4 | | -(x+3)+(2x-1)=(1+4x)+(3+x) | | -6+2x=20 | | a^2+1=0 | | -20+7x=-118 |

Equations solver categories